Dosimetric comparison of anterior posterior-posterior anterior 2-field three-dimensional conformal radiotherapy, 4-field three-dimensional conformal radiotherapy and forward plan intensity modulated radiotherapy techniques in female lymphoma patients irradiated to neck and mediastinum - ALSAN ÇETİN, İLKNUR (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2018)
Aim: Dosimetric comparison of three different techniques in female lymphoma patients who had radiotherapy (RT) to the neck and mediastinum. Setting and Design:: Retrospective clinical study. Materials and Methods: Computerized tomography-simulator images of eight patients were obtained retrospectively. Using 6 MV-X photon energy, RT plans were formed with three different techniques (anterior posterior-posterior anterior 2-field three-dimensional conformal RT [AP-PA 2-field 3D-CRT], 4-field 3D-CRT and forward plan intensity modulated RT [FPIMRT]). Comparisons were in terms of homogeneity index (HI), conformity index (CI), and inhomogeneity coefficient for planning target volume (PTV); mean lung dose, V-5Gy, V-10Gy, V-20Gy, V-30Gy for lung; D-mean, V-7.5Gy, V-15Gy, V-25Gy for heart; D-mean, V-3.5Gy, V-10Gy, V-20Gy for breast; D-max for spine; D-mean, V-10Gy, V-18Gy, V-25Gy, V-30Gy for thyroid. Statistical Analysis Used: Since nonparametric tests had to be used due to the study population being < 30, Friedman and Wilcoxon signed-rank tests were implemented in trilateral and bilateral comparison of techniques, respectively. For statistical significance, P value was required to be <0.05. Results: When FPIMRT was compared with AP-PA and 4-field techniques with respect to, HI (AP-PA/FPIMRT P: 0.017; 4-field/FPIMRT P: 0.03) and CI (AP-PA/FPIMRT P: 0.018; 4-field/FPIMRT P: 0.042), FPIMRT was more advantageous. In addition, FPIMRT was found more useful in terms of D-max (AP-PA/FPIMRT P: 0.012; 4-Field/FPIMRT P: 0.012) for spinal cord and D-mean (AP-PA/FPIMRT P: 0.012; 4-field/FPIMRT P: 0.012) for thyroid. Conclusion: FPIMRT was superior in terms of PTV homogeneity and conformity. However, it was observed that for normal tissues, FPIMRT was advantageous only for spinal cord and thyroid; but it was not the most advantageous technique for some of the dose-volume parameters of the breast, lung, and heart.
Keywords: Dose-volume parameters; female; forward plan intensity modulated radiotherapy; lymphoma; three-dimensional conformal radiotherapy; HODGKINS-LYMPHOMA; HEART-DISEASE; RADIATION; CANCER; CHEMOTHERAPY